2020
DOI: 10.1111/age.12920
|View full text |Cite
|
Sign up to set email alerts
|

A de novo germline mutation of KIT in a white‐spotted Brown Swiss cow

Abstract: SummaryWhite‐spotting coat colour phenotypes in cattle are either fixed characteristics of specific cattle breeds or occur sporadically owing to germline genetic variation of solid‐coloured parents. A Brown Swiss cow showing a piebald pattern resembling colour‐sidedness was referred for genetic evaluation. Both parents were normal solid‐brown‐coloured cattle. The cow was tested negative for the three known DNA variants in KIT, MITF and TWIST2 associated with different depigmentation phenotypes in Brown Swiss c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…As the first exon encodes only the 5 -UTR sequence and 22 out of the 979 amino acids (MRGARGAWDLLCVLLVLLRGQT) of the signal peptide, the generated deletion can be referred to as the Kit gene knockout. Several research groups have demonstrated that the white or white-spotting phenotype represents genetic mutations in the locus near and including the Kit gene (transmembrane tyrosine kinase receptor) in various organisms, such as alpacas [58], camels [59,60], cats [61], cows [62,63], dogs [64], donkeys [65], goats [66], horses [67], mice [68][69][70], pigs [71], rabbits [72], rats [73], yaks [74], humans [75,76], and even zebrafish [77]. The molecular mechanism behind this phenotype is linked to melanocyte migration and survival maintained by tyrosine-protein kinase KIT receptor.…”
Section: Large Unexpected Deletion In the Target Regionmentioning
confidence: 99%
“…As the first exon encodes only the 5 -UTR sequence and 22 out of the 979 amino acids (MRGARGAWDLLCVLLVLLRGQT) of the signal peptide, the generated deletion can be referred to as the Kit gene knockout. Several research groups have demonstrated that the white or white-spotting phenotype represents genetic mutations in the locus near and including the Kit gene (transmembrane tyrosine kinase receptor) in various organisms, such as alpacas [58], camels [59,60], cats [61], cows [62,63], dogs [64], donkeys [65], goats [66], horses [67], mice [68][69][70], pigs [71], rabbits [72], rats [73], yaks [74], humans [75,76], and even zebrafish [77]. The molecular mechanism behind this phenotype is linked to melanocyte migration and survival maintained by tyrosine-protein kinase KIT receptor.…”
Section: Large Unexpected Deletion In the Target Regionmentioning
confidence: 99%
“…These results suggest that there are other factors involved that can affect the inheritance of the amount of white. Novel mutations within the KIT gene are still being discovered in other species such as cattle [ 4 ] or horses [ 6 ] and it’s possible that additional changes in a cat’s KIT gene are yet to be found. Other genes and interactions between them may be also involved [ 8 , 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…White spots are present in many mammals such as horses, mice, cattle, dogs etc. [ 4 , 5 , 6 , 7 , 8 ]. In 1919, Whiting [ 9 ] mated cats and studied the inheritance of varying amounts of white-spotting.…”
Section: Introductionmentioning
confidence: 99%